Generation of Oligodendrocyte Progenitor Cells From Mouse Bone Marrow Cells - Zhang, Yuan; Lu, Xin-Yu; Casella, Giacomo; Tian, Jing; Ye, Ze-Qing; Yang, Ting; Han, Juan-Juan; Jia, Ling-Yu; Rostami, Abdolmohamad; Li, Xing (Frontiers in Cellular Neuroscience, 2019)
Oligodendrocyte progenitor cells (OPCs) are a subtype of glial cells responsible for myelin regeneration. Oligodendrocytes (OLGs) originate from OPCs and are the myelinating cells in the central nervous system (CNS). OLGs play an important role in the context of lesions in which myelin loss occurs. Even though many protocols for isolating OPCs have been published, their cellular yield remains a limit for clinical application. The protocol proposed here is novel and has practical value; in fact, OPCs can be generated from a source of autologous cells without gene manipulation. Our method represents a rapid, and high-efficiency differentiation protocol for generating mouse OLGs from bone marrow-derived cells using growth-factor defined media. With this protocol, it is possible to obtain mature OLGs in 7-8 weeks. Within 2-3 weeks from bone marrow isolation, after neurospheres formed, the cells differentiate into Nestin+ Sox2+ neural stem cells (NSCs), around 30 days. OPCs specific markers start to be expressed around day 38, followed by RIP+O4+ around day 42. CNPase+ mature OLGs are finally obtained around 7-8 weeks. Further, bone marrow-derived OPCs exhibited therapeutic effect in shiverer (shi) mice, promoting myelin regeneration and reducing the tremor. Here, we propose a method by which OLGs can be generated starting from bone marrow cells and have similar abilities to subventricular zone (SVZ)-derived cells. This protocol significantly decreases the timing and costs of the OLGs differentiation within 2 months of culture.